A COMPARISON OF TWO PHYSICAL GUIDANCE PROCEDURES IN THE TREATMENT OF PEDIATRIC FOOD REFUSAL. (17th October 2013) - Borrero, Carrie S. W.; Joseph Schlereth, G.; Rubio, Emily K.; Taylor, Tessa
<x xml:space="preserve">Abstract</x> Physical guidance procedures can be effective in the treatment of severe pediatric food refusal. Researchers evaluating the use of physical guidance procedures often include a procedure referred to as a jaw prompt, but other variations of physical guidance may also be effective. An additional form of physical guidance, the finger prompt, might increase food acceptance. We evaluated nonremoval of the spoon and physical guidance (jaw prompt or finger prompt) in a reversal design. Results showed treatment packages including both procedures were effective in increasing food acceptance and decreasing inappropriate mealtime behavior. Copyright © 2013 John Wiley & Sons, Ltd.